Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2): Codon Usage and Replicative Fitness - Kanduc, Darja (Global Medical Genetics, 2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) codon usage, as shown by the polyprotein coding sequence, shows better translation potential in the human host when compared with human coronavirus OC43 (HCoV-OC43) codon usage. Such translational advantage might facilitate SARS-CoV-2 replication, immunogenicity, and pathogenicity, thus also accounting for the less harmful character of HCoV-OC43 infection.
Keywords: codon usage; HCoV-OC43; SARS-CoV-2; viral replication fitness